The future of war a history - Freedman, Lawrence (New York : Public Affairs, 2017)
For as long as there have been wars there have been fears bout the next war. where are the new dangers? what is the best defense? how might peace come about? This is the history of how over the last 150 years we have tried-rightly and wrongly- to predict war's future.
Includes bibliographical references and index.
Keywords: War--Forecasting.